Cash Holdings and Firm Performance in the Restaurant Industry (Journal of Applied Business and Economics, 2023)
This study explores the link between cash holdings and performance outcomes in public restaurant companies in the United States, leveraging the critical role played by the industry context. We hypothesize that cash holdings have positive associations with both short-term and long-term firm performance in the restaurant industry. Our empirical analyses, based on fixed-effect regression models that control for all time-invariant variables, reveal that holding cash can improve performance in the restaurant industry, in support of our hypotheses.
Keywords: business; diversity; cash holdings; industry context; firm performance